Evaluasi Keamanan Ikan Asap di Dusun I Epil Kecamatan Lais Kabupaten Musi Banyuasin - Anton Fuadi; Agus Supriadi; Rodiana Nopianti (Jurnal FishtecH, 2015)
The objective research was to identify and analyze the safety level of smoked fish at traditional processing unit of Epil I, District of Lais, Musi Banyuasin. The research method used descriptive method. Sample was taken from three producers of smoked fish at traditional processing unit of Epil I, District of Lais, Musi Banyuasin. The highest water content of smoked fish was at the third producer (13.13+0.21%) and the lower at the first producer (10.14+3.65%). The highest salt content of smoked fish was at the first producer (0.87+0.35%) and the lower at the third producer (0.84+0.25%). The highest water activity was at the third producer (0.57+0.08) and the lower at the first producer (0.44+0.11). The highest peroxide was at the second producer (5.38+3.15 mg/kg) and the lower at the first producer (5.07+2.47 mg/kg). The highest mold test was at the third producer (3820 cfu/g) and the lower at the first Producer (2560 cfu/g). The highest heavy metal was at the third producer (11.96+9.54 mg/kg) and the lowes at the first producer is 7.11+7.16 mg/kg.